The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.11138/ccmbm/2015.12.3s.031
|View full text |Cite
|
Sign up to set email alerts
|

The role of imaging in diagnosis and management of femoral head avascular necrosis

Abstract: SummaryThe aim of this paper is to critically review the literature documenting the imaging approach in adult Femoral Head Avascular Necrosis (FHAVN). For this purpose we described and evaluated different radiological techniques, such as X-ray, Computed Tomography (CT), Magnetic Resonance Imaging (MRI), and Nuclear Medicine. Plain films are considered the first line imaging technique due to its ability to depict femoral head morphological changes, to its low costs and high availability. CT is not a routinely p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 61 publications
1
29
0
Order By: Relevance
“…In accordance with the literature, we found that all osteonecrotic lesions could be detected with T1 fast spin-echo and short T1 inversion-recovery sequences, and therefore, diffusion-weighted and PET images probably can be omitted (28). For the detection of anthracycline-induced cardiomyopathy, ventricular volumes and ejection fractions are important metrics.…”
Section: Discussionsupporting
confidence: 87%
“…In accordance with the literature, we found that all osteonecrotic lesions could be detected with T1 fast spin-echo and short T1 inversion-recovery sequences, and therefore, diffusion-weighted and PET images probably can be omitted (28). For the detection of anthracycline-induced cardiomyopathy, ventricular volumes and ejection fractions are important metrics.…”
Section: Discussionsupporting
confidence: 87%
“…Hip MRI signal strength reflects a variety of pathological changes in the femoral head. For example, T1 sequences appear as high signals indicating the presence of oedema [37] . A high signal in ONFH generally demonstrates that violent changes have taken place in the bone structure.…”
Section: Mri Signal Analysismentioning
confidence: 99%
“…Femoral head AVN is considered to be a common cause of musculoskeletal weakening and is a major diagnostic and remedy challenge [8,9]. Its estimated that almost 50% of patients with femoral head AVN will experience extreme joint deterioration and around three years after the initial diagnosis they will require a hip arthroplasty which is known as a major surgical procedure [10,11].…”
Section: Introductionmentioning
confidence: 99%